2015
DOI: 10.1038/pr.2015.226
|View full text |Cite
|
Sign up to set email alerts
|

Maternal high-fat hypercaloric diet during pregnancy results in persistent metabolic and respiratory abnormalities in offspring

Abstract: Background:We have shown in a previous population-based study significant correlation between childhood asthma and early abnormalities of lipid and glucose metabolism. This study's specific aim was to determine whether maternal nutrition in pregnancy affects postnatal metabolic and respiratory outcomes in the offspring.Methods:On gestation day 1, dams were switched from standard chow to either high-fat hypercaloric diet or control diet. Terminal experiments were performed on newborn and weanling offspring of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 32 publications
6
42
1
Order By: Relevance
“…We now show increased AHR in offspring of both early and combined in utero and later life HFD exposure. By varying diets at weaning, our results differ from a previously published rat model of HFD exposure at pregnancy onset showing increased airway reactivity in weanling offspring and adult rats that continued on HFD (Griffiths et al 2016). Those authors reported but did not show any differences between HFD cross at weaning in the offspring.…”
Section: Discussioncontrasting
confidence: 99%
“…We now show increased AHR in offspring of both early and combined in utero and later life HFD exposure. By varying diets at weaning, our results differ from a previously published rat model of HFD exposure at pregnancy onset showing increased airway reactivity in weanling offspring and adult rats that continued on HFD (Griffiths et al 2016). Those authors reported but did not show any differences between HFD cross at weaning in the offspring.…”
Section: Discussioncontrasting
confidence: 99%
“…Among other mechanisms, consumption of a high‐fat diet during pregnancy may contribute to the development of asthma in offspring. Indeed, structural changes, higher level of cytokines and increased airway resistance have been observed in rats born from mothers fed a high‐fat diet during gestation . Similar structural changes have been observed in lung epithelial cells in adult mice fed with a high‐fat diet .…”
Section: Obesity and Asthmasupporting
confidence: 53%
“…87 More importantly, pups born to dams fed a HFD diet during gestation exhibit impaired antigen-specific immune responses as evidenced by: (a) higher mortality rates in an E. coli sepsis model; (b) increased bacterial burden; (c) larger abscesses following Methicillin-resistant Staphylococcus aureus infection 87 ; and exacerbated respiratory disease following infection with respiratory syncytial virus. 88,89 Furthermore, in utero HFD exposure resulted in reduced production of IL-6 and TNF by splenocytes following ex vivo LPS stimulation. In contrast, IL-17, IL-6, and TNF production by colonic lamina propria lymphocytes was significantly higher in pups born to HFD-fed dams following stimulation.…”
Section: Maternal Obesity and Alterations In Offspring Lymphoid Tissumentioning
confidence: 99%
“…One key study concluded that gestational HFD exposure results in fewer splenic lymphocytes and thinner thymic cortex . More importantly, pups born to dams fed a HFD diet during gestation exhibit impaired antigen‐specific immune responses as evidenced by: (a) higher mortality rates in an E. coli sepsis model; (b) increased bacterial burden; (c) larger abscesses following Methicillin‐resistant Staphylococcus aureus infection; and exacerbated respiratory disease following infection with respiratory syncytial virus . Furthermore, in utero HFD exposure resulted in reduced production of IL‐6 and TNFα by splenocytes following ex vivo LPS stimulation.…”
Section: Introductionmentioning
confidence: 99%